AGILTY TRAINING MODEL FOR CHILGREN WITH DOWN SYNDROME DISABILITIES - Rayhan, Ilyassyah; Apriana Sanga Dwi, Dicky Reva; Sukriadi, Slamet; Arif, Muhamad; Nurulfa, Rizky; Hernawan, Hernawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research was conducted on athletes with Down syndrome Soina Jakarta. The research time was approximately 4 months starting from February to May 2023. The number of subjects in this study were 12 athletes with disabilities, consisting of 6 boys and 6 girls. The research method used in this research is Research and developmentor R&D according to Borg and Gall (1983). There were 20 training models created, after going through various stages and improvements, 20 models were declared valid and suitable for practice provided that they always pay attention to safety in practice and work from easy to difficult. Data collection was carried out in 2 ways, firstly, namely filling out a questionnaire by the athlete's parents and secondly, by collecting data directly. Data collection in this research isone group pre-test post-testData processing from the results obtained is assisted by the IBM SPSS 25 for Windows program system, normality test values >0.05 are normally distributed, reliability test values >0.05 are normally distributed or valid, validity tests with distribution >0.05 are considered valid, test homogeneity and the hypothesis can be concluded that the agility abilities of athletes with Down syndrome disabilities have increased